Penyuluhan Hukum tentang Pelanggaran Lalu Lintas Kepada Pelajar di Aceh Utara - Johari; Husni, Husni; Sumiadi (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2023)
Traffic violation data from the Lhoksukon Police Traffic Directorate shows that the number of traffic violations continues to increase. If strategic steps are not taken to increase public awareness of legal compliance, it will result in loss of property and loss of life. Strategies or efforts to increase public legal awareness as road users are basically part of orderly traffic. Strategies to increase public legal awareness include outreach or campaigns to comply with traffic regulations and build a disciplined community character. This character formation can begin through the example of teachers, parents, religious and community leaders. Therefore, through this counseling, the character of discipline can be transmitted to all high school students around the jurisdiction of the Lhokseukon Police, North Aceh